Time to laugh funny tales from here and there - Fenner, Phyllis Reid 1899- (Knopf, 1942)
Twenty humorous stories, told or retold by Hans Christian Andersen, Lucretia P. Hale, Ruth Sawyer, Parker Fillmore, Seumas MacManus, and Howard Pyle.